Groups in Context: A Model of Group Effectiveness - Baninajarian, Narges; Abdullah, Zulhamri (Eurojournals, 2009)

(untitled)
The primary aim of this paper is to determine the factors influencing group effectiveness in student-based groups. This study also develops a model of group effectiveness based on literature reviews of organizational work teams and group effectiveness. Qualitative research methods, interviews and document review, were employed to achieve the objectives of this study. The framework integrates two sets of factors influencing group effectiveness: group structure and individual characteristics. The model fills a gap in the group effectiveness literature review by developing research propositions that take into account different theoretical perspectives to study group effectiveness.